Distribuição temporal e ontogenia alimentar de larvas e juvenis de Pachyurus bonariensis Steindachner, 1879 (Perciformes, Sciaenidae) da baía Sinhá Mariana, Rio Cuiabá, Mato Grosso. - Santin, Miriam (2007)
The information of the ictiica community cannot be considered appropriate without a good knowledge of natural history and the initial phases of the life cycle. In such a way, this work has the objective to study the abundance, the distribution and feeding of larvae and juvenile of Pachyurus bonariensis of the Sinhá Mariana bay, Cuiabá River, Mato Grosso. The samplings had been carried through in the period of March from 2000 to March of 2004, being that the larvae were always captured the 4:00 p.m. and 10:00 p.m. The juvenile were collected using drag nets, operated in the nocturnal period. Simultaneously, water samples were collected for the obtaining of the temperature, dissolved oxygen, pH and electric conductivity. In laboratory, the larvae were separate and identified. For the distribution study and abundance of larvae, they were grouped by development stages (preflexion, flexion and postflexion) and for the feeding study the larvae and juvenile were contained in size class, established in agreement with the interval among the lengths minimum pattern (2,1 mm) and maximum (49,4 mm) and also for development stages. The temporary variation of the density of larvae, it was analyzed through the Analysis of Bifactorial Variance. The association between the environmental variables and the larvae was accomplished through the Pearson Correlation. For the analysis of the feeding data, they were determined the Frequency of Occurrence, the Specific Abundance, the niche width and the association of the diet enters the different size classes. During the period, the largest densities of larvae happened between the months of October and January (spring-summer), being this the main period of reproduction of the species. However, larvae in preflexion and flexion were also found in the months of winter (June and July), possibly associated to the favorable conditions for the reproduction. During the period of studies, individuals of all the stages were present, evidencing a reproductive seasonality, as well as the use of the bay Sinhá Mariana for the reproduction and development. The density of larvae in the subsurface of the water is larger at night, mainly of the larvae more developed, while the initial larvae are found in the subsurface of the water in both schedules, in other words, the degree of larval development influences in the distribution pattern. Regarding the feeding of the larvae and juvenile, it is observed that the mouth, initially is wide and it occupies terminal position, providing larger capture of foods. Already in the end of the postflexion stage and juvenile, the mouth becomes more funneled, assuming position subterminal, whose reflex is the alteration of the feeding and habitat. The characteristic proctratil of the mouth in the larvae in the end postflexion and in the juvenile ones, it assists the food search. The folds of the digesting tube and the formation of the cecos during the ontogenic development coincide with the change of the diet. The microcrustaceans were the main itens consumed by the larvae of the first four classes, what characterizes them as zooplanktivoruos. In the fifth class, just composed for juvenile, they were found larvae and mainly, Chironomidae pupa characterizing the diet as invertivorous. During the larval development the feeding strategy is generalist, they explored available feeding resources in the middle. Already in the fifth class, the feeding strategy is specialist, due to a high consumption of a single prey, Chironomidae larvae. The initial increase of the niche width is related to the decrease of the morphologic limitations while the narrowing starting from the third class it can be associated to the morphology of the mouth and change of the diet. The similarity of the diet among the classes is due the grade alteration of the diet according to the development of the larvae and of the juvenile ones. The activity of the larvae is larger at night probably this is a mechanism to minimize the intraespecific competition and to reduce the predation on the larvae.